1976
DOI: 10.1111/j.1528-1157.1976.tb03396.x
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effects of Imipramine in Experimental Models of Epilepsy

Abstract: In a variety of laboratory models of experimental epilepsy, imipramine exerts a biphasic action on the CNS as manifested by antiepileptic properties at low doses and convulsant effects at higher doses. In mice, imipramine (17.5-25 mg/kg, i.p.) blocks maximal electroshock seizures while exerting little or no effect on pentylenetetrazol-induced seizures. In cats, imipramine (2.5-15 mg/kg, i.v.) reduces penicillin and estrogen-induced epileptiform discharge, shortens afterdischarge duration and elevates afterdisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The anticonvulsive profile of the agents obtained in this study, e.g., transient effectiveness with considerable interindividual variation, is quite different from those of phenytoin, phenobarbital, car-CONTROL bamazepine, ethosuximide, clorazepate (Wada et al, 1976a,b;Wada, 1980), as well as sodium valproate (Sato et al, 1977;Wada, 1980), all of which have been studied using the kindling model of epilepsy. The observed transient and non-dose-dependent anticonvulsive effect of these agents is shared by nomifensine (Sato et al, 1978), imipramine (Lange et al, 1976), and amphetamine (Riffee and Gerald, 1976). Since these three drugs are known to facilitate neurotransmission through interference with reuptake and/or the accentuated release of brain catecholamines, and since both TRH-t and DN-14 17 accelerate the release of catecholamines, the observed anticonvulsive effects in this study are likely mediated through catecholaminergic mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…The anticonvulsive profile of the agents obtained in this study, e.g., transient effectiveness with considerable interindividual variation, is quite different from those of phenytoin, phenobarbital, car-CONTROL bamazepine, ethosuximide, clorazepate (Wada et al, 1976a,b;Wada, 1980), as well as sodium valproate (Sato et al, 1977;Wada, 1980), all of which have been studied using the kindling model of epilepsy. The observed transient and non-dose-dependent anticonvulsive effect of these agents is shared by nomifensine (Sato et al, 1978), imipramine (Lange et al, 1976), and amphetamine (Riffee and Gerald, 1976). Since these three drugs are known to facilitate neurotransmission through interference with reuptake and/or the accentuated release of brain catecholamines, and since both TRH-t and DN-14 17 accelerate the release of catecholamines, the observed anticonvulsive effects in this study are likely mediated through catecholaminergic mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…Biphasic action of imipramine was observed in mice and cats. Imipramine at lower doses exhibited a protective action in penicillin and estrogen-induced seizures in cats [62], cocaine-induced seizures in mice [63] and MES, but it did not inhibit pentylenetetrazole (PTZ)-induced convulsions in mice [62]. This antidepressant at higher doses aggravated cocaine-induced seizures in mice [63], chemically-and electrically-induced seizures in cats [62], while at doses of above 20-25 mg/kg i.p.…”
Section: Imipraminementioning
confidence: 89%
“…Low dosages of imipramine or amitriptyline were found to raise the maximal electroshock and pentetrazol seizure thresholds in mice (Sigg 1959;Vernier 1961). Further studies in different experimental models of epilepsy showed that imipramine has a biphasic effect since at low dosages the drug blocks the maximal electroshock seizures in mice, but induces clonic seizures at high dosages (Lange et al 1976). Trimble and colleagues (1977) found that the intravenous administration of clomipramine or imipramine lowers the convulsive threshold in the photosensitive baboon Papio papio.…”
Section: Ll Tricyclic Antidepressantsmentioning
confidence: 97%